Positive and Negative Themes Found in Superhero Films. (December 2017) - Bauer, Matthew; Georgeson, Andrew; McNamara, Caitlin; Wakefield, Bryan H.; King, Tonya S.; Olympia, Robert P.
Superhero films have become incredibly popular. The objective of this study was to determine the positive and negative themes found in a select number of superhero films. A total of 30 superhero films were analyzed. The average numbers of positive and negative themes were 19.4 and 29.5 mean events per hour for all included films, respectively. The most common positive themes were "assisting others/protecting the public, " "positive relationships with family/friends, " and "teamwork/collaboration." The most common negative themes were "acts of violence/fighting, " "use of guns/knives/lethal weapons, " and "bullying/intimidation/torture." Based on the superhero films included in our study, the number of negative themes, especially acts of violence, outweighs positive themes. Although an exposure to positive themes found in superhero films may be beneficial to the development of children, pediatric health care providers should counsel children and their families in an attempt to limit their exposure to violence.